On the town in New York : the landmark history of eating, drinking, and entertainments from the American Revolution to the food revolution /: the landmark history of eating, drinking, and entertainments from the American Revolution to the food revolution. (1999) - Batterberry, Michael; Batterberry, Ariane Ruskin
No abstract available